Thyroid function in end stage renal disease and effects of frequent hemodialysis. Issue 4 (16th March 2017) - Lo, Joan C.; Beck, Gerald J.; Kaysen, George A.; Chan, Christopher T.; Kliger, Alan S.; Rocco, Michael V.; Li, Minwei; Chertow, Glenn M.
Abstract: Introduction: End‐stage renal disease (ESRD) is associated with perturbations in thyroid hormone concentrations and an increased prevalence of hypothyroidism. Few studies have examined the effects of hemodialysis dose or frequency on endogenous thyroid function. Methods: Within the Frequent Hemodialysis Network (FHN) trials, we examined the prevalence of hypothyroidism in patients with ESRD. Among those with endogenous thyroid function (without overt hyper/hypothyroidism or thyroid hormone supplementation), we examined the association of thyroid hormone concentration with multiple parameters of self‐reported health status, and physical and cognitive performance, and the effects of hemodialysis frequency on serum thyroid stimulating hormone (TSH), free thyroxine (FT4), and free tri‐iodothyronine (FT3) levels. Conventional thrice‐weekly hemodialysis was compared to in‐center (6 d/wk) hemodialysis (Daily Trial) and Nocturnal (6 nights/wk) home hemodialysis (Nocturnal Trial) over 12 months. Findings: Among 226 FHN Trial participants, the prevalence of hypothyroidism was 11% based on thyroid hormone treatment and/or serum TSH ≥8 mIU/mL. Among the remaining 195 participants (147 Daily, 48 Nocturnal) with endogenous thyroid function, TSH concentrations were modestly (directly) correlated with age (r = 0.16, P = 0.03) but not dialysis vintage. Circulating thyroid hormone levels were not associated with parameters of health status or physical and cognitive performance. Furthermore, frequent in‐center and nocturnal hemodialysis did not significantly change (baseline to month 12) TSH, FT4, or FT3 concentrations in patients with endogenous thyroid function. Discussion: Among patients receiving hemodialysis without overt hyper/hypothyroidism or thyroid hormone treatment, thyroid indices were not associated with multiple measures of health status and were not significantly altered with increased dialysis frequency.